Environmental Flow Assessments Are Not Realizing Their Potential as an Aid to Basin Planning - King, Jackie M.; Brown, Cate (Frontiers in Environmental Science, 2018)
Multiple planned dams in developing countries, mostly for hydropower, are threatening some of the world’s great river systems. Concern over their social and environmental impacts has led to hydropower being excluded from the sustainability term ‘green energy’. Better planning, design and operation of hydropower dams could guide where to build and not to build, and how to mitigate some of their negative impacts. Impact assessments presently done for dams include Cumulative Impact Assessments (CIAs) or similar at the basin level, and Environmental Impact Assessments at the project level. These typically do not detail how the river ecosystem could change and the implications for its dependent social structures. A comprehensive Environmental Flows (EFlows) Assessment does provide this information but is almost always not linked to the other impact assessments. When done at all, it is often rudimentary; rarely basin-wide; and almost always done after major development decisions have already been made. A more effective approach for any basin targeted for hydropower or other large dam development would be to formally and automatically embed the requirement for a basin-wide, detailed EFlows Assessment into a CIA. This should be done at the earliest stage of planning, before dam sites are selected and allocated to developers. The EFlows method adopted matters, as it dictates the scope and flexibility of a study. Rapid one-size-fits-all methods do not provide the detail that governments and other stakeholders need to understand the possible future of their river basins, negotiate and make informed decisions.